Pola makan dan anemia ibu dengan kejadian BBLR: analisis data Indonesian Family Life Survey (IFLS 5) - Ulva, Siti Maria; Hakimi, Mohammad; Kandarina, Istiti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2022)
Dietary pattern and anemia with the occurrence of LBW babies: Indonesian Life Family Survey (IFLS 5)Background: Nutritional problems occur throughout the human life cycle. Maternal, infant, and neonatal mortality rates are critical national growth indicators. The most common cause of death in neonates is babies with low birth weight (LBW). Objective: This study examines the association between diet, anemia, and the incidence of LBW in Indonesia using the Indonesia Family Life Survey (IFLS) wave 5. Methods: This observational study used IFLS 5 secondary data. The study population is women of reproductive age (15-49 years), married, had their last child born alive, and their weight weighed. The independent variables were diet and anemia, while the dependent was LBW. Effect modifiers were age, parity, education, employment, pregnancy complications, consumption of iron tablets, and residence. Results: The total number of respondents was 2,368, with an LBW incidence of 8.7%. The percentage of non-diverse diets is 72.3%, more than diverse diets. There was a significant relationship between diverse dietary patterns and LBW. A less varied diet provides a 1.32 more substantial risk of giving birth to an LBW baby compared to mothers with a diverse diet. However, there was no relationship between anemia and LBW. Further analysis showed two food groups significantly associated with LBW: nuts and meat and fish. Conclusions: A diverse diet lowers the risk of LBW but is not significantly related. Efforts are needed to improve community nutrition through a varied and balanced diet. Social factors related to LBW are mothers' education and employment.